PERAN KOMPETENSI DAN MOTIVASI TERHADAP KINERJA INDIVIDU KELOMPOK WANITA TANI DI KABUPATEN KULON PROGO - Fitri Rahmawati (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2019)
The purpose of this study was to analyze the role of competence and motivation in improving the performance of individual members of farmer women groups in Kulon Progo Regency. The population in this study were members of the farmer women group. The sampling technique uses saturated samples, namely members of farmer women groups in Lendah District with 71 respondents. The data collection method uses a questionnaire with a Likert scale as an alternative choice of answers and interviews. The questionnaire test instrument has fulfilled the competency, motivation and performance validity requirements with r counts above 0.3610 and competency reliability is 0.946, motivation reliability is 0.837 and the performance reliability of individual members of farmer women groups is 0.891 so it meets the requirements of the validity and reliability test. Data analysis techniques with the SPSS 19.0 program, using simple linear regression analysis with a value of the competency regression coefficient (X1) of 0.022 with a significance of less than (<0.05), means that H1 is accepted. The results of a simple linear regression analysis with a coefficient of work with a significance of 0.048 baseline with significance (<0.005), means H2 is accepted. The results of the study indicate that increasing the individual performance of members of farmer women groups is strongly influenced by the role of competencies that members have in increasing their expertise and the role of motivation of members in driving the cooperation of women farmer groups. Competence and motivation are strongly influenced by the strength of building a spirit of self-development, moving the team, the spirit of sharing knowledge, and creating comfort and security at work, as well as training provided from groups or the Government and related agencies, to provide strength in the development of women's groups farmer.